2015
DOI: 10.1007/s10393-015-1089-1
|View full text |Cite
|
Sign up to set email alerts
|

Improving Wellbeing and Environmental Stewardship Through Volunteering in Nature

Abstract: Environmental volunteering (EV) can provide a unique way to optimise the wellbeing of participants while fostering environmental stewardship. However, the potential of EV to create human health benefits remains an under-researched area. This study provides evidence for improved wellbeing and mood state for 32 participants from diverse backgrounds undertaking EV activities. Most participants also reported improved environmental stewardship with a greatly improved understanding of the environment and the need to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 8 publications
6
22
0
Order By: Relevance
“…Volunteers were also found to be more extroverted and optimistic and to perceive a greater sense of control in their lives than non‐volunteers. In a small survey sample of mostly marginalised individuals, Molsher and Townsend () discovered that environmental volunteering led to significant improvements in general well‐being and mood states. In an exit interview, most participants attributed these improvements to the social aspect of the volunteering program and to learning about the environment.…”
Section: Benefits Of Volunteeringmentioning
confidence: 99%
“…Volunteers were also found to be more extroverted and optimistic and to perceive a greater sense of control in their lives than non‐volunteers. In a small survey sample of mostly marginalised individuals, Molsher and Townsend () discovered that environmental volunteering led to significant improvements in general well‐being and mood states. In an exit interview, most participants attributed these improvements to the social aspect of the volunteering program and to learning about the environment.…”
Section: Benefits Of Volunteeringmentioning
confidence: 99%
“…However, another study found that the quality of green spaces had a stronger bearing on health outcomes than quantity [26]. Other studies linked mental wellbeing with social activity, including volunteering, in green spaces [27,28]. Green spaces can enable newcomers and migrants to feel a sense of belonging through activities such as community gardening [29,30].…”
mentioning
confidence: 99%
“…The influence of environmental 'harms' to public mental health have been well-studied (e.g. for air quality 70 ; the effect of climate change on health 71,72 ; food-borne toxins and poor diets 18, 73, well-being, with scholars going 'beyond toxicity' , to assess the benefits of engaging with the natural environment and in initiatives that seek to 're-green' the human environment 76,77,78 .…”
Section: What Is Already Known About This Topicmentioning
confidence: 99%